GADAI TANAH PERTANIAN DI DESA PAKRAMAN LUMBUNG GEDE KECAMATAN SELEMADEG BARAT KABUPATEN TABANAN BALI - , I Wayan Wahyu Wira Udytama; , Prof. Dr. Sudjito Bin Atmodirejo, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to find out how the implementation of agricultural land mortgage, the impacts posed by article 7 of Law Prp 56 th 1960 and to resolving conflicts posed by mortgage of agricultural land. Writers take 8 cases of agricultural land mortgage transaction to sample, all of them are rural communities Pakraman Lumbung Gede. They fill kuisioner closed. In addition, the author also interviewed the Kelian adat and a public figure. Results of this study are, Mortgage of agricultural land is done by way of assignment of the respective parties, the chargor assign treatment and the right to enjoy the fruits of his agricultural land to agricultural land mortgage buyer. Given impact of Article 7 of Law No. 56 PRP Th 1960 provides mortgage period for agricultural land sidelines though not the meaning of the provisions of Article 7.Conflicts resolved by peaceful means, using means of dialogue, negotiation for consensus.